Construction of pseudorabies virus variant attenuated vaccine: codon deoptimization of US3 and UL56 genes based on PRV gE/TK deletion strain - Mengwei Xu; Mengwei Xu; Mengwei Xu; Mengwei Xu; Laixu Zhu; Laixu Zhu; Laixu Zhu; Laixu Zhu; Aimin Ge; Yamei Liu; Yamei Liu; Yamei Liu; et al. (Frontiers in Microbiology, 2023)
Since 2011, pseudorabies based on the pseudorabies virus (PRV) variant has emerged as a serious health issue in pig farms in China. The PRV gE/TK or gE/gI/TK deletion strains protect against emerging PRV variants. However, these variants may cause lethal infections in newborn piglets without PRV antibodies. Previous studies have shown that codon deoptimization of a virulence gene causes virus attenuation. Accordingly, we deoptimized US3-S (US3 gene encoding a short isoform that represents approximately 95% of the total US3 transcription) and UL56 genes (first 10 or all codons) of PRV gE/TK deletion strain (PRVΔTK&gE−AH02) to generate six recombinant PRVs through bacterial artificial chromosome technology. In swine testicular cells, recombinant PRVs with all codon deoptimization of US3-S or UL56 genes were grown to lower titers than the parental virus. Notably, US3-S or UL56 with all codon deoptimization reduced mRNA and protein expressions. Subsequently, the safety and immunogenicity of recombinant PRVs with codon deoptimization of US3-S or UL56 are evaluated as vaccine candidates in mice and piglets. The mice inoculated with recombinant PRVs with codon deoptimization of US3-S or UL56 showed exceptional survival ability without severe clinical signs. All codons deoptimized (US3-S and UL56) significantly decreased virus load and attenuated pathological changes in the brains of the mice. Moreover, the protection efficiency offered by recombinant PRVs with codon deoptimization of US3-S or UL56 showed similar effects to PRVΔTK&gE−AH02. Remarkably, the 1-day-old PRV antibody-negative piglets inoculated with PRVΔTK&gE-US3-ST−CD (a recombinant PRV with all codon deoptimization of US3-S) presented no abnormal clinical symptoms, including fever. The piglets inoculated with PRVΔTK&gE-US3-ST−CD showed a high serum neutralization index against the PRV variant. In conclusion, these results suggest using codon deoptimization to generate innovative live attenuated PRV vaccine candidates.